Detection of Cytomegalovirus in Patients with Inflammatory Bowel Disease: Where to Biopsy and How Many Biopsies?. Issue 12 (December 2015) - McCurdy, Jeffrey D.; Enders, Felicity T.; Jones, Andrea; Killian, Jill M.; Loftus, Edward V.; Bruining, David H.; Smyrk, Thomas C.
Abstract : Background: The potential negative impact of cytomegalovirus (CMV) in ulcerative colitis (UC) and Crohn's disease (CD) warrants efforts to improve the yield of diagnostic techniques. Methods: We retrospectively determined the optimal biopsy location and number from sixty-eight patients with inflammatory bowel disease (66% UC, 31% CD, and 3% inflammatory bowel disease-unclassified) with CMV disease between 2005 and 2011. Biopsies with endoscopic and histologic inflammation were analyzed by immunohistochemistry and/or in situ hybridization. The proportion of positive biopsies was determined, and using data from the 25th percentile, we assessed the number of biopsies required to achieve an 80% probability of a single positive biopsy. Results: Of the patients with a diagnosis by immunohistochemistry and/or in situ hybridization, 27 of 61 (44%; 95% confidence interval, 32–57) were positive by hematoxylin and eosin, and 11 of 36 (31%; 95% confidence interval, 16–46) had systemic CMV by polymerase chain reaction. Of the patients with biopsies proximal and distal to the splenic flexure, 1 of 11 with UC and 4 of 8 with CD had a diagnosis limited to the right colon. Twenty percent of biopsies were positive by immunohistochemistry or in situ hybridization (20% in UC and 17% in CD). Eleven biopsies in UC and 16 in CD were required to achieve an 80% probability of a positive biopsy. Conclusions: Biopsy location and number are important considerations when assessing for CMV. We recommend a flexible sigmoidoscopy with 11 biopsies in UC and a colonoscopy with 16 biopsies in CD. Abstract : Article first published online 13 August 2015.